The Influence of Brand Image, Packaging Blister and Product Placement in Korean Dramas on Kopiko Candy Purchase Decisions - Suestri; Sri Riyanti; Ramlah Puji Astuti (Indonesian Journal of Business Analytics, 2025)
One of the many strategies implemented by Kopiko candy to expand its market reach is product placement in Korean dramas. This study aims to investigate and examine the influence of brand image, blister packaging, and product placement in Korean dramas on the purchasing decisions of Kopiko candy. This is an associative study using quantitative data. The population in this study consists of Indonesian individuals who have purchased Kopiko candy and have watched Korean dramas. The sample size is 100 individuals, selected using purposive sampling with the following criteria: Indonesian citizens who have bought Kopiko at least once and have watched one or more of the following Korean dramas: Vincenzo, Hometown Cha-Cha-Cha, Yumi's Cells, Mine, Little Women, Today's Webtoon, and Taxi Driver. The analysis method used is multiple linear regression analysis. The findings of the study indicate that overall, brand image, blister packaging, and product placement in Korean dramas have a significant and positive influence on Kopiko candy purchasing decisions. When analyzed partially, each variable—brand image, blister packaging, and product placement—also shows a significant and positive impact on purchasing decisions.